A QSPR Study for the Prediction of the pKa of N-Base Ligands and Formation Constant Kc of Bis(2, 2′-bipyridine)Platinum(II)-N-Base Adducts Using Quantum Mechanically Derived Descriptors. (15th October 2012) - Palaz, Selami; Türkkan, Baki; Eroğlu, Erol
Abstract : Quantitative structure-property relationship (QSPR) study on the acid dissociation constant, p Ka of various 22 N-base ligands including pyridines, pyrimidines, purines, and quinolines has been carried out using Codessa Pro methodology and software. In addition, the formation constant, Kc of these ligands with Pt(II)( bpy ) 2 2 + (bpy = 2, 2′-bipyridine) ion has also been modelled with the same methodology. Linear regression QSPR models of p Ka and Kc were established with descriptors derived from AM1 calculations. Among the obtained QSPR models of p Ka presented in the study, statistically the most significant one is a four parameters linear equation with the squared correlation coefficient, R 2 values of ca. 0.95 and the squared cross-validated correlation coefficient, R c v 2 values of ca. 0.89, and external the squared correlation coefficient, R ext . 2 values of ca. 0.97. Statistically the most significant QSPR model of Kc is also a four parameters linear equation with the squared correlation coefficient, R 2 values of ca. 0.75 and the squared cross-validated correlation coefficient, R c v 2 values of ca. 0.55, and external the squared correlation coefficient, R ext . 2 values of ca. 0.81. An analysis of descriptors that involved in the p Ka models indicate that reactivity index and charge distribution related descriptors play major roles to model acid dissociation constant of ligands of N bases.